Annual Plan 2004-2005 Volume II Uttar Pradesh - Planning Commission (Planning Commission, 2004)
Summary Statement of Major Headwise - Outlays and Expenditure , Summary Statement of Sub-Major Headwise - Outlays and Expenditure , Sub-Major Headwise - Outlays and Expenditure , Physical Targets and Achievements , Prime Minister Gramodaya Yojna - Outlays and Expenditure , Prime Minister Gramodaya Yojna - Physical Targets and Achievements , Centrally Sponsored Schemes - Outlays and Expenditure , District Plan - Outlays and Expenditure , XII Voluntary Sector - Outlays and Expenditure , Women Component (WC) - Outlays and Expenditure , Women Component (WC) - Physical Targets and Achievements
Annual Plan 2004-2005 Volume II
Government of Uttar Pradesh